Max Mosley and the English Right to Privacy - James E. Stanley (Washington University Global Studies Law Review, 2011)
The Article presents information related to the English rights to privacy. It further states that for a long time England had been denying the existence of privacy tort and discusses the emergence of de facto rights to privacy due to the influence of European Convention on Human Rights. It also discusses the opinions and demands of Max Mosley in this issue and the decisions of the trial Mosley v. United Kingdom.
Keywords: Actions & amp; defenses (Law); De facto doctrine; Judgments; Right of privacy – Great Britain; Max Mosley; Convention for the Protection of Human Rights & amp; Fundamental Freedoms (1950)